Proceedings of the 36th Annual International Symposium on Lattice Field Theory — PoS(LATTICE2018) 2019
DOI: 10.22323/1.334.0060
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of systematic error in hadronic vacuum polarization contribution to muon g-2

Abstract: We study systematic uncertainties in the lattice QCD computation of hadronic vacuum polarization (HVP) contribution to the muon g − 2. In this proceedings we investigate two systematic effects; finite volume (FV) effect, mass correction and cutoff effect. We evaluate FV effect at the physical pion mass on two different volumes of (5.4 fm) 4 and (10.8 fm) 4 using PACS10 configurations at the same cutoff scale, and for the mass correction, we compare two different pion mass points, m π = 135 MeV and 146 MeV pion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…For isospin-symmetric lattice-QCD simulations in which the pions in the loops have the mass of the π 0 , the model predicts slightly larger finitevolume corrections, ∼ (14−31) × 10 −10 . For comparison, preliminary lattice-QCD studies by the PACS and RBC/UKQCD collaborations find finite-volume shifts of ∆a ll µ (conn.) 5.4 fm → 10.8 fm = 40(18) × 10 −10 [44] and ∆a ll µ (conn.) 4.66 fm → 6.22 fm = 21.6(6.3) × 10 −10 [45], respectively, which are not in disagreement with our model given their large statistical uncertainties.…”
Section: Lattice Corrections and Continuum Extrapolationmentioning
confidence: 99%
“…For isospin-symmetric lattice-QCD simulations in which the pions in the loops have the mass of the π 0 , the model predicts slightly larger finitevolume corrections, ∼ (14−31) × 10 −10 . For comparison, preliminary lattice-QCD studies by the PACS and RBC/UKQCD collaborations find finite-volume shifts of ∆a ll µ (conn.) 5.4 fm → 10.8 fm = 40(18) × 10 −10 [44] and ∆a ll µ (conn.) 4.66 fm → 6.22 fm = 21.6(6.3) × 10 −10 [45], respectively, which are not in disagreement with our model given their large statistical uncertainties.…”
Section: Lattice Corrections and Continuum Extrapolationmentioning
confidence: 99%
“…∆a LO-HVP µ,ud (5.4 fm, 10.8 fm) = 40(18) [42] though the statistical error is large and has overlap to the other results. Thus, the FV effect tends to become larger by taking account of various mode contributions besides the lowest pion mode.…”
Section: Figurementioning
confidence: 79%
“…Finite volume (FV) effects in the vector correlator are dominated by the two-pion state and can thus be expected to be important for large time separations t. Various studies (see, e.g. [26,20,16,27]) of FV effects for lattice calculations of a HVP µ suggest that these are of the order of ∆ FV a HVP µ ≈ 20 − 30 × 10 −10 for typical sizes of 5 − 6 fm of state-of-the-art lattice ensembles used at the physical point. Thus, it is crucial to carefully study and correct for FV effects when aiming at percent level precision for the HVP.…”
Section: Finite Volume Effectsmentioning
confidence: 99%
“…A straightforward way to study finite volume effects is using ensembles that differ only in the volume. Figure 6 shows results from the PACS collaboration [26] for the a HVP µ integrand calculated using two different volumes of 5.4 fm and 10.8 fm at the physical pion mass. One can clearly see, a significant difference between the data on both ensembles, in particular for larger values of t. The authors of [26] found finite volume effects for a HVP µ to be about 1.7 times larger than what was expected from next-to-leading order (NLO) Chiral Perturbation Theory (χPT).…”
Section: Finite Volume Effectsmentioning
confidence: 99%
See 1 more Smart Citation